(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Traditional cost accounting is aimed at identifying costs that are incurred on an ongoing basis in connection with operating activities. The concept that supports the decision-making process in the long term is strategic cost management. The purpose of the article is to identify the tools for strategic decision-making in cost management focused on the corporate strategy of an enterprise. It is determined that strategic cost management is a process of making decisions on specific cost drivers in the context of the company’s development strategy and value chain. An enterprise should evaluate its value chain in comparison with similar chains of competitors. The article presents a methodology for such an assessment. It is proved that strategic management is based on the following assumptions: connection with the value chain, strategic positioning of the enterprise, analysis of cost drivers, the client is the starting point for decision-making and activities, which results in the adoption of the market price as the basis for cost planning and product development, implementation of cost management in the early stages of the product life cycle, since the cost is largely determined by the product features determined at the stage of its design and development. A key element of targeted analysis is cost estimation in terms of the impact of specific factors (drivers). Strategic cost drivers are determined based on the implementation of the development strategy and its connection with the value chain. There are two main types of them: structural cost drivers and implementation cost drivers. It is substantiated that strategic cost management involves the use of product life cycle costing. Depending on the phases of the product life cycle, various management methods based on basic models are used: "ABC-Costing, Target-Costing. Strategic positioning of the company in terms of costs incurred should be carried out by means of cost benchmarking, which is aimed at comparing the costs incurred by the company and its competitors. The subject of comparisons is the cost of processes that allow achieving a competitive advantage.